2020
DOI: 10.1523/jneurosci.0290-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dopaminergic Neurons That Can Both Establish Associative Memory and Acutely Terminate Its Behavioral Expression

Abstract: An adaptive transition from exploring the environment in search of vital resources to exploiting these resources once the search was successful is important to all animals. Here we study the neuronal circuitry that allows larval Drosophila melanogaster of either sex to negotiate this exploration-exploitation transition. We do so by combining Pavlovian conditioning with high-resolution behavioral tracking, optogenetic manipulation of individually identified neurons, and EM data-based analyses of synaptic organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 74 publications
(151 reference statements)
2
51
2
Order By: Relevance
“…In other associative conditioning experiments using DAN-i1 activation as a reward, decreased attraction to the odor was observed in the reverse-paired groups [9,43,44]. In our experiments, we did not see any evidence of increased aversion in the reverse-paired groups.…”
Section: Paired Co 2 Presentation and Optogenetic Activation Of A Single Pair Of Reward Neurons Eliminates Co 2 Avoidancecontrasting
confidence: 59%
See 1 more Smart Citation
“…In other associative conditioning experiments using DAN-i1 activation as a reward, decreased attraction to the odor was observed in the reverse-paired groups [9,43,44]. In our experiments, we did not see any evidence of increased aversion in the reverse-paired groups.…”
Section: Paired Co 2 Presentation and Optogenetic Activation Of A Single Pair Of Reward Neurons Eliminates Co 2 Avoidancecontrasting
confidence: 59%
“…Here our results differed from those previously reported. In other as-says, presenting the reward (including via activation of DAN-i1) prior to presenting the conditioned odor results in decreased attraction/increased avoidance [9,44] of that odor. We found that such "reversepairings" neither increased nor decreased a larva's avoidance of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…DANs also make direct connections with MBONs in each MB compartment, and optogenetic activation of PAM11 DANs can directly excite MBON07 with slow dynamics ( Takemura et al, 2017 ). This might provide a mechanism to temporarily suppress memory expression without impairing the underlying memory, which is stored as depressed KC-to-MBON synapses ( Krashes et al, 2009 ; Schleyer et al, 2020 ; Senapati et al, 2019 ; Takemura et al, 2017 ). For example, DANs are known to control hunger and thirst-dependent memory expression ( Krashes et al, 2009 ; Senapati et al, 2019 ), and their excitation of MBONs could provide a possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We note that transferring the brains directly to pure Bouin’s solution would lead to a collapse of the tissue. The fixation time was 7 min, at room temperature on a shaker; initial experiments with fixation in 4% paraformaldehyde (PFA) had failed for the primary mouse anti‐ChR2 antibody mentioned below (data not shown, see also Weiglein, Gerstner, Mancini, Schleyer, & Gerber, 2019, Schleyer et al, 2020). Then, the larval brains were washed three times consecutively in fresh washing solutions for 10 min each time, using 0.2% PBT (Triton‐X‐100, CAS: 9036‐19‐5, Roth, Karlsruhe, Germany; in 1x PBS).…”
Section: Methodsmentioning
confidence: 99%